THE EFFECT OF PRE-SERVICE SCIENCE AND MATHEMATICS TEACHERS' AI LITERACY AND ETHICAL USE OF INFORMATION TECHNOLOGIES ON THEIR ETHICAL REFLECTIONS ON AI - Erdogan, Fatma; Tutak, Tayfun; Polat, Mehmet (Sci Methodical Ctr-Sci Educologica, 2026)
The growing presence ofartificial intelligence (AI) in education raises critical questions about teachers' AI literacy and ethical reflection. This study aims to examine the effects of pre-service science and mathematics teachers' AI literacy and their ethical use of information technologies on their ethical reflections on AI. The study, designed as a correlational survey, included 219 pre-service science and mathematics teachers from a university in Eastern T & uuml;rkiye. Data were collected using three instruments: the Artificial Intelligence Literacy Scale, the Information Technologies Ethical Use Scale, and the Artificial Intelligence Ethical Reflection Scale. The findings indicate that, although pre-service teachers demonstrate high levels of knowledge in the technical and critical dimensions ofAI, they remain at a moderate level in translating this knowledge into practical application and in engaging in ethical reasoning. Structural equation modelling results indicate that AI literacy significantly and directly influences ethical reflection on AI, whereas the ethical use of information technologies constitutes a weaker predictor. The mediation analysis further reveals that general ethical use of information technologies does not play a significant mediating role in the relationship between AI literacy and ethical reflection on AI.
Keywords: artificial intelligence (AI) ethics; artificial intelligence (AI) literacy; information technology (IT); mathematics education; science edu cation